Break up the right way

Calculus Level 3

d x x 6 + x 4 = ? \large \int \frac{dx}{x^6 + x^4} = \ ?

Notation: C C denotes the constant of integration.

1 3 x 3 1 x + ln x + C \frac { -1 }{ 3{ x }^{ 3 } } -\frac { 1 }{ x } +\ln { x } +C 1 3 x 3 1 x + arctan x + C \frac { -1 }{ 3{ x }^{ 3 } } -\frac { 1 }{ x } +\arctan { x } +C 1 3 x 3 + 1 x + ln x + C \frac { 1 }{ 3{ x }^{ 3 } } +\frac { 1 }{ x } +\ln { x } +C 1 3 x 3 + 1 x + arctan x + C \frac { -1 }{ 3{ x }^{ 3 } } +\frac { 1 }{ x } +\arctan { x } +C

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Saurabh Saurabh
Aug 17, 2015

Q u e s . d x x 6 + x 4 = d x x 4 ( x 2 + 1 ) = d x ( x 2 + 1 x 2 ) x 4 ( x 2 + 1 ) = [ 1 x 4 1 x 2 ( x 2 + 1 ) ] = [ 1 x 4 x 2 + 1 x 2 x 2 ( x 2 + 1 ) ] = [ 1 x 4 1 x 2 ) + 1 1 + x 2 ] 1 3 x 3 + 1 x + arctan x Ques.\quad \int { \frac { dx }{ { x }^{ 6 }+{ x }^{ 4 } } } \\ =\int { \frac { dx }{ { x }^{ 4 }({ x }^{ 2 }+1) } } \\ =\int { \frac { dx({ x }^{ 2 }+1-{ x }^{ 2 }) }{ { x }^{ 4 }({ x }^{ 2 }+1) } } \\ =\int { \left[ \frac { 1 }{ { x }^{ 4 } } -\frac { 1 }{ { x }^{ 2 }({ x }^{ 2 }+1) } \right] } \\ =\int { \left[ \frac { 1 }{ { x }^{ 4 } } -\frac { { x }^{ 2 }+1-{ x }^{ 2 } }{ { x }^{ 2 }({ x }^{ 2 }+1) } \right] } \\ =\int { \left[ \frac { 1 }{ { x }^{ 4 } } -\frac { 1 }{ { x }^{ 2 }) } +\frac { 1 }{ 1+{ x }^{ 2 } } \right] } \\ \Rightarrow \frac { -1 }{ 3{ x }^{ 3 } } +\frac { 1 }{ x } +\arctan { x }

When you apply partial fractions , you get , d x x 6 + x 4 = [ 1 x 2 + 1 x 4 + 1 x 2 + 1 ] d x \int \frac{dx}{x^6+x^4} = \int [-\frac{1}{x^2} + \frac{1}{x^4} + \frac{1}{x^2+1}]dx The integration of which is, 1 x 2 = 1 x , 1 x 4 = 1 3 x 3 , 1 x 2 + 1 = t a n 1 x / a r c t a n x \int \frac{-1}{x^2} = \frac{1}{x} , \int \frac{1}{x^4} = \frac{-1}{3x^3},\int \frac{1}{x^2+1} = tan^{-1}x / arctan x So we get, d x x 6 + x 4 = 1 3 x 3 + 1 x + a r c t a n x + c \int \frac{dx}{x^6+x^4} =\displaystyle \boxed{ \dfrac {-1}{3x^3} + \dfrac{1}{x} +arctan x + c}

Correct your solution's last line .. it should be -1/(3x^2) not -1/(x^2)

rishabh singhal - 5 years, 9 months ago

Log in to reply

Thanx for telling me.Ive edited it :)

Athiyaman Nallathambi - 5 years, 9 months ago
Daniel Ferreira
Sep 6, 2015

Neste problema devemos aplicar a técnica de integração por partes. Inicialmente, devemos trabalhar com o integrando. Segue,

1 x 6 + x 4 = 1 x 4 ( x 2 + 1 ) 1 x 6 + x 4 = A x + B x 2 + C x 3 + D x 4 + E x + F x 2 + 1 1 x 6 + x 4 = A ( x 2 + 1 ) x 3 + B ( x 2 + 1 ) x 2 + C ( x 2 + 1 ) x + D ( x 2 + 1 ) + ( E x + F ) x 4 x 4 ( x 2 + 1 ) \\ \frac{1}{x^6 + x^4} = \frac{1}{x^4(x^2 + 1)} \\\\\\ \frac{1}{x^6 + x^4} = \frac{A}{x} + \frac{B}{x^2} + \frac{C}{x^3} + \frac{D}{x^4} + \frac{Ex + F}{x^2 + 1} \\\\\\ \frac{1}{x^6 + x^4} = \frac{A(x^2 + 1)x^3 + B(x^2 + 1)x^2 + C(x^2 + 1)x + D(x^2 + 1) + (Ex + F)x^4}{x^4(x^2 + 1)}

Resolvendo o sistema formado obtemos: A = 0 , B = 1 , C = 0 , D = 1 , E = 0 , F = 1 \boxed{A = 0}, \; \boxed{B = - 1}, \; \boxed{C = 0}, \; \boxed{D = 1}, \; \boxed{E = 0}, \; \boxed{F = 1} .

Portanto,

d x x 6 + x 4 = 1 x 2 d x + 1 x 4 d x + 1 x 2 + 1 d x d x x 6 + x 4 = ( x 1 + c 1 ) + ( x 3 3 + c 2 ) + ( tan 1 x + c 3 ) d x x 6 + x 4 = 1 x 1 3 x 3 + tan 1 x + C \int \frac{dx}{x^6 + x^4} = \int \frac{- 1}{x^2} \, dx + \int \frac{1}{x^4} \, dx + \int \frac{1}{x^2 + 1} \, dx \\\\\\ \int \frac{dx}{x^6 + x^4} = (x^{- 1} + c_1) + (- \frac{x^{- 3}}{3} + c_2) + (\tan^{- 1} x + c_3) \\\\\\ \boxed{\boxed{\int \frac{dx}{x^6 + x^4} = \frac{1}{x} - \frac{1}{3x^3} + \tan^{- 1} x + C}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...